The influence of food packaging elements in consumer food purchase decision / Zulfaiq Nazarudin - Nazarudin, Zulfaiq (2014)
Previous study shows that, packaging is not only for protecting the products but can be more advanced in marketing world such as being a vehicle for communication of the products, medium of advertising and also branding the products for competition in the markets. It becomes increasingly important because most of the companies nowadays tend to focus more on packaging especially food packages products. However, past studies conducted stated that due to increasing self-service and changing consumer’s lifestyle, the consumer’s interest in packaging elements keep changing from visual elements to informational elements. Therefore, there are different results and findings came out from the research done. In order to know more better on packaging elements, this study was conducted to determine the influence of food packaging elements in consumer food purchase decision. It will be analyzed and examined by using two major independent variables which are visual elements that consists of graphics and colors, and shapes and sizes and informational elements such as product information and technology. One theoretical framework, conceptual model of packaging elements and purchase decision is considered appropriate and has been conducted by Silayoi and Speece (2004). Apart from that, 100 questionnaires were distributed equally at three different hypermarkets (Tesco, Mydin and Aeon Jusco) for the people that consumed the food products at Melaka Tengah area to gain data and add depth to findings from the content analysis. By conducting the correlation test, this study could identify the relationship between all food packaging elements towards consumer purchase decision. Based on the results obtained in chapter four, it can be concluded that visual elements has a strong relationship in influencing consumer purchase decision on food packaging compared to informational elements. This shows that most of consumer in Malaysia especially Melaka Tengah area are purchasing the food products based on the visual elements of food packaging. . From the results obtained, it can also be concluded that shapes and sizes is the strongest item from visual elements and product information is the strongest item from informational elements that affect consumer purchase decision.